-759C>T Polymorphism of the HTR2C Gene is Associated with Second Generation Antipsychotic-Induced Weight Gain in Female Patients with Schizophrenia - Daray, Federico Manuel; Rodante, Demián; Carosella, Laura G.; Silva, María Elena; Martínez, Melina; Fernández Busch, María V.; Faccone, Diego F.; Rothlin, Rodolfo P.; Maffía, Paulo C. (Pharmacopsychiatry, 2017)
Introduction: The HTR2C gene is an important candidate in pharmacogenetic studies of antipsychotic-induced weight gain (AIWG). However, inconsistent results have been obtained. The present study investigated the association between -759C>T, functional polymorphism of the HTR2C receptor, and AIWG.Methods: A prospective cohort of 48 female inpatients with schizophrenia and related illness treated according to normal clinical practice with second generation antipsychotics (SGAs) risperidone, clozapine, quetiapine, and olanzapine were evaluated. Patients were weighted at admission and again at 6 weeks of hospitalization. Weight gain was defined as an increase≥7% of baseline weight. The association between polymorphisms HTR2C and weight gain was evaluated. Multiple logistic regression was run to determine potential confounders.Results: Patients with the T allele at position -759 (TT or CT) gained less weight as compared to patients who did not have the allele. This association was not affected by possible confounding factors such as age, baseline BMI, and prior psychopharmacological treatment.Discussion: The T allele at position -759 protects against AIWG in female patients with schizophrenia.
Keywords: second generation antipsychotic; weight gain; HTR2C gene; schizophrenia